Experimentální vyhodnocení efektivity sušení recipientu pomocí vybraných vakuových technik - Lagron, Luděk (Jihočeská univerzita, 2022)
This bachelor thesis deals with the application of three different vacuum drying techniques with respect to their efficiency. These are the direct drying method, drying with inert gas dosing, and drying with a cycling period. The aim of the thesis is the vacuum drying of the interspace in a container serving for storage of used nuclear fuel; the thesis faces the problem solved in the Temelín nuclear power plant. The thesis introduces the problematics of used nuclear fuel storage in containers, the basics of vacuum technology, and finally reports the results of experiments to verify and evaluate the most effective method of vacuum drying.
Experimental evaluation of recipient drying efficiency using vacuum techniques
Keywords: vakuum; Jaderná elektrárna; palivo; těsnost; vakuování; sušení; vyhořelé palivo; helium; vacuum; nuclear power plant; fuel; tightness; vacuuming; drying; spent fuel; helium